67.8k views
4 votes
for each expression combine like terms and write an equivalent expression with fewer terms1. 10x-5+3x-22. 4 - 2x + 5x

1 Answer

3 votes

10x+5+3x-2

You can operate just similar terms, similar terms in the given equation are:

10x and 3x

5 and -2

Then, you get:


\begin{gathered} =(10x+3x)+(5-2) \\ =13x+3 \end{gathered}

-------------------------------------


4-2x+5x

Similar terms:

-2x and 5x


\begin{gathered} =4+(-2x+5x) \\ =4+3x \end{gathered}

User Leejoy
by
6.1k points